(untitled) (International Seven Journal of Multidisciplinary, 2023)
The paper introduces the central theme with a brief overview of the historical evolution of bridges, highlighting the materials and construction methods used in each historical period. Still brings a summary of each type of bridge and constructions methods employed throughout the history of engineering. Furthermore, this work includes case study analyses addressing the design of slab bridges, conducting a literature review of academic studies that have been conducted, and comparing them to the preliminary design guidelines proposed in the Special Structures Design Manual of DNER. The results indicate that the slab thicknesses recommended in the manual resulted in larger structural dimensions compared to those used in the case studies, but they remained within the same order of magnitude. Additionally, the rates of steel used in bridge slabs were calculated, and these values closely approximated of a value mentioned in technical literature.